A compact unc45b‐promoter drives muscle‐specific expression in zebrafish and mouse. Issue 8 (9th July 2016) - Rudeck, Steven; Etard, Christelle; Khan, Muzamil M.; Rottbauer, Wolfgang; Rudolf, Rüdiger; Strähle, Uwe; Just, Steffen
Abstract : Summary: Gene therapeutic approaches to cure genetic diseases require tools to express the rescuing gene exclusively within the affected tissues. Viruses are often chosen as gene transfer vehicles but they have limited capacity for genetic information to be carried and transduced. In addition, to avoid off‐target effects the therapeutic gene should be driven by a tissue‐specific promoter in order to ensure expression in the target organs, tissues, or cell populations. The larger the promoter, the less space will be left for the respective gene. Thus, there is a need for small but tissue‐specific promoters. Here, we describe a compact unc45b promoter fragment of 195 bp that retains the ability to drive gene expression exclusively in skeletal and cardiac muscle in zebrafish and mouse. Remarkably, the described unc45b promoter fragment not only drives muscle‐specific expression but presents heat‐shock inducibility, allowing a temporal and spatial quantity control of (trans)gene expression. Here, we demonstrate that the transgenic expression of the smyd1b gene driven by the unc45b promoter fragment is able to rescue the embryonically lethal heart and skeletal muscle defects in smyd1b ‐deficient flatline mutant zebrafish. Our findings demonstrate that the described muscle‐specific unc45b promoter fragment might be a valuable tool for the development of genetic therapies in patients suffering from myopathies. genesis 54:431–438, 2016. © 2016 The Authors. Genesis Published by Wiley Periodicals, Inc.